Voltage clamp of cat motoneurone somata: properties of the fast inward current. - Barrett, J N (1980)
1. The soma membrane of cat spinal motoneurones was voltage clamped using separate intracellular voltage and current electrodes directed into the same motoneurone with a new guide system. 2. Antidromic stimulation of the motoneurone's axon or small depolarizing voltage clamp steps (10-20 mV from the resting potential) evoked a small (30-80 nA) all-or-none action potential current, which was shown by occlusion experiments to originate from the initial segment of the axon. Except for this axonal current spike, there was no indication of active (voltage-dependent) conductance changes in membrane regions not under good voltage clamp control. Calculations based on motoneuronal geometry, and electrophysiological recordings from spinal cord neurones in tissue culture, indicate that the proximal portions of dendritic membranes were also under good voltage clamp control. 3. Clamp depolarizations greater than 20 mV activated a fast, transient inward current, which increased in a smoothly graded manner with depolarization between 20 and 40 mV from the resting potential, reaching a peak magnitude of up to 450 nA, and then decreased smoothly for larger depolarizations. Extrapolation of the current-voltage relationship for this current indicated a reversal potential about 80-116 mV positive to the resting potential. 4. This transient inward current is blocked by tetrodotoxin. After a depolarizing voltage clamp step the conductance system controlling this current first activates with fast, non-linear kinetics, and then inactivates with first-order kinetics. These properties are similar to those of the Na conductance system in squid and frog axons. 5. Conditioning-testing experiments showed that the time constant of inactivation ranges from 1.0-1.3 msec at potentials slightly negative to the resting potential to 0.1-0.3 msec for depolarizations 60 mV from the resting potential. The degree of steady-state inactivation also varied with membrane potential, ranging from total inactivation at depolarizations greater than 30 mV from the resting potential, to minimal inactivation at potentials more than 10 mV negative to the resting potential.